The Effect of Social Media to the Brand Awareness of a Product of a Company - Hansel Bagus Tritama; Riswan Efendi Tarigan (Bina Nusantara University, 2016)
Social media is an online media, where the users can easily participate, share, and create any content such as banner, posters, videos and advertisement. Many companies use these social media as a tool to promote their products and make customers aware with their brand. On the other hand, not all companies succeed to market their products and make their products are at their customers’ awareness. The purpose of this research is to find the correlation between social media commu- nication marketing with companys brand awareness in social media. The research method for this research is quantitative research. This method collects data with explanative research type which explains the relationship between two variables. The result of this research is to show that marketing communication in a company has an impact to company’s brand awareness. In addition, this research wants to show that marketing via social media can give impact to company’s revenue. The summary of this research is to get significant information about the effect of social media toward companys brand awareness through quantitative and explanative research method due to the rising of social media.